Place of residence and coach-athlete relationship predict drop-out from competitive cross-country skiing - Marit Anita Schmid; Guro Strøm Solli; Rune Kjøsen Talsnes; Rune Kjøsen Talsnes; Frode Moen (Frontiers Media S.A., 2023)
The current study investigated whether factors such as living residence, the coach-athlete working alliance, goal orientation, and intrinsic motivation could explain drop-out, and whether these factors differed between athletes included in the elite- vs. general sport programs during high school years. In total 257 cross-country skiers, graduated from three different Norwegian Top Sport schools during the period from 2015 to 2019, were recruited to retrospectively investigate their experiences related to the time period when they participated in programs for cross-country skiing at high school. In total 116 of these athletes completed an online survey including validated and standardized instruments for the assessment of the coach-athlete working alliance (CAWAI), goal orientation (GO), perceived satisfaction with their performances (PAP) and intrinsic motivation (IM). The results showed that 84% of the athletes had dropped out from cross-country skiing, while 16% were still active. The highest ranked fixed statements of causes for drop-out was "a natural choice" (3.79 ± 1.11), "priority of education or work" (3.61 ± 1.30), "lack of motivation" (3.49 ± 1.28), "negative performance development" (3.46 ± 1.18), and "challenges with health" (3.25 ± 1.54). There were significant differences between active and drop-out in scores for reciprocity between the coaches' and the athletes' perceptions of goals (CAWAI-goal; 5.87 ± .98 vs. 5.07 ± 1.15; p = .004), the coach-athlete relationship bond (CAWAI-bond; 6.08 ± .91 vs. 5.07 ± 1.38; p = .001), and tasks chosen to reach the defined goals (CAWAI-task; 5.61 ± .92 vs. 4.90 ± 1.09; p = .006). Furthermore, active athletes had higher mastery orientation (22.11 ± 2.88 vs. 20.00 ± 3.74; p = .010). A hierarchical binary logistic regression analysis showed that place of residence and the coach-athlete working alliance were significant predictors of drop-out while mastery and performance goal orientation or intrinsic motivation were not significant. All five predictors explained 23% of the variability in drop out from cross-country skiing. Overall, 58% and 42% of the athletes participated in the elite and general programs for cross-country skiing during high school, respectively. The athletes that took part in the elite programs reported significantly stronger coach-athlete working alliances (CAWAI-sum; 14.46±3.10 vs. 14.28±3.37; p = .000), higher mastery orientation (21.19±3.50 vs. 19.36±3.66; p = .008), and performance satisfaction (PAP; 19.17±5.98 vs. 15.69±5.19; p = .001) compared to the athletes attending general programs. The results are discussed in terms of existing knowledge on how place of residence, the coach-athlete working alliance, goal orientation, performances, and motivation might impact drop-out in cross-country skiing.